Bridging Theory and Practice: A Conceptual Study on Experiential Learning in Student Entrepreneurship - Rong, Gu Yu; Nasir, M Khalid M; Mansor, Ahmad Zamri (South Asian Journal of Social Sciences and Humanities, 2025)
Experience learning is a principal pathway in closing the gap between theoretical knowledge and practical application in student entrepreneurship. This conceptual study looks into the role of experiential learning in building entrepreneurial skills, stimulating innovation, and improving students' business acumen. The study highlights how experiential learning models, such as action-based learning, simulations, internships and incubators of startups, enable entrepreneurial competency to a great extent. The importance of real-world engagement is also highlighted as building students' problem-solving abilities, as they can build risk-taking mindsets and adaptability in dynamic business environments. However, the study also discusses the difficulties and prospects of experiential learning within entrepreneurship education. The results guide the design of effective entrepreneurship programs.
Keywords: Experiential learning; Entrepreneurial Education; Entrepreneurship Education; Innovation